Edge of excellence: JEC's Scopus achievement, doors 2025 breakthroughs, and Volume 4 Issue 1 (2025) highlights - Serhiy O. Semerikov; Tetiana A. Vakaliuk (Journal of Edge Computing)
This editorial highlights recent edge computing advancements from the doors 2025 workshop and JEC Volume 4, Issue 1, while celebrating the journal's acceptance into Scopus. The paper examines innovative solutions addressing distributed systems challenges, including IoT-based monitoring systems, intelligent traffic prediction algorithms, and security implementations for resource-constrained environments. Architectural frameworks like Akka for smart grids and edge-deployed large language models represent significant technological developments. The editorial acknowledges Scopus indexing as recognition of the journal's scientific integrity and the collaborative efforts of the editorial community. It demonstrates how edge computing continuously evolves to optimise resources, reduce latency, and enhance security across diverse networked ecosystems.